Chemical safety in Stockholm schools: Support and guidance from the Education Administration for 170 municipal schools - Gullstrand, Jonny (LUMAT-B: International Journal on Math, Science and Technology Education, 2023)
This abstract outline the efforts of the Education Administration at the city of Stockholm to promote chemical safety in our schools. Emphasizing the schools' obligation to prevent illness and accidents, the Education Administration offers support and guidance to ensure a safe teaching environment for chemistry. There are a total of 170 municipal schools in Stockholm, of which 80 of them have chemistry and science education. These include both junior high schools (year 7–9) and senior high schools (year 10–12). Upper stages before going to college.